The dynamics of effective classroom management in secondary schools from a faculty perspective - Yusef Yaqoub Shahda; Sabih Karam Zamil Al Kinani (Zanco Journal of Humanity Sciences)
The research aimed to identify the dynamics of effective classroom management in secondary schools from the perspective of faculty members